E – Governance and Rural Development of India - Abidin, Shafiqul (International Journal of Computer Sciences and Engineering, 2025)
In spite of poverty, poor infrastructure India is moving smoothly and feasibly towards digital India. But due to unawareness and some other known and unknown reasons the policy-makers in India tend to justify the adoption and expansion of e-governance in India. Obviously and truly e-governance is the key factor for the Good Governance in developed and developing countries like India.